Understanding selected health outcomes between Kansas counties: does where a county falls on a rural urban classification continuum matter? - Breese, Katie (Kansas State University, 2016)
Purpose: The objective of this study was to compare characteristics of urban and rural counties in Kansas in order to identify and seek explanations for differences in health factors and population health outcomes. Methods: Select data from the County Health Rankings and Roadmaps program were examined within or using the context of the USDA, Economic Research Service 2013 Rural-Urban Continuum Code (RUC) classification scheme. A comparison of all 19 urban counties vs. all 86 rural counties was conducted, followed by a comparison of counties as they were classified on the rural-urban continuum. Findings: More evidence of health disparities was observed when using the rural-urban continuum comparison than by the strict urban vs. rural comparison. Health determinants, behaviors, and outcomes, were generally more unfavorable in rural counties, but this was mostly captured through the RUC comparison. On average, RUC 4 and RUC 5 communities (both rural) were most disadvantaged when compared to counties that fell somewhere else on the continuum. Overall, there were higher rates of injury death, preventable hospital stays, and premature death in rural areas. Conclusions: The favorable and unfavorable health factors and health outcomes did not present only in urban areas nor only in rural areas nor did they present only in one RUC. These findings showed that there is a complexity to health disparities that cannot be easily captured or addressed without careful attention to the nature of the specific communities in which they are found.
Keywords: Health disparities; Health outcomes; Rural; Urban